A new measurement algorithm for TDR-based localization of large dielectric permittivity variations in long-distance cable systems. (April 2021) - Cataldo, Andrea; De Benedetto, Egidio; Masciullo, Antonio; Cannazza, Giuseppe
Abstract: One of the most common applications of time-domain reflectometry (TDR) is the localization of dielectric permittivity variations (DPVs) along cable systems. However, signal attenuation and dispersion phenomena limit the usability of TDR when used on long cable systems. Some TDR measuring instruments offer the possibility of modifying the amplitude and the width of the TDR test pulse signal, along with the gain of the input stage amplifier. Increasing these parameters generally allows to investigate longer distances; nevertheless, increasing the gain may saturate the instrument analog to digital converter (ADC) and increasing the pulse width leads to worse spatial resolution. For this reason, it is customary for the operator to repeat TDR measurements several times, with different settings, and proceed by focusing each time on a different TDR reflectogram; however, this procedure is time-consuming and, eventually, it does not guarantee optimal performance. Starting from these considerations, in this work, a new measurement algorithm for facilitating and making more effective the TDR-based localization of large DPVs on long cable systems is proposed. The algorithm automatically acquires several TDR reflectograms obtained by setting different values of the gain of the input stage amplifier and the values of the pulse width of the test signal. The reflectograms are then automatically processed, in an effort to balance the short-distance resolution and long-distance gain in a single composite reflectogram (CR), which can be conveniently used also by non-skilled operators. The developed algorithm was implemented and validated through experiments on a practical case study to localize DPVs on a 300 m-long cable system. Highlights: New strategy for enhancing detectability of dielectric permittivity variations in long cables. The proposed algorithm employs TDR measurements. The algorithm balances short-distance resolution and long-distance gain. The resulting composite reflectogram can be conveniently used also by nonskilled operators. The developed algorithm was validated through experiments on a practical case study.